Synthesis of Spherical Silica by Sol-Gel Method and Its Application as Catalyst Support - Anirut Leksomboon; Bunjerd Jongsomjit (Department of Chemical Engineering, Universitas Gadjah Mada, 2011)
In this present study, the spherical silica support was synthesized from tetraethyloxysilane (TEOS), water, sodium hydroxide, ethylene glycol and n-dodecyltrimethyl ammonium bromide (C12TMABr). The particle size was controlled by variation of the ethylene glycol co-solvent weight ratio of a sol-gel method preparation in the range of 0.10 to 0.50. In addition, the particle size apparently increases with high weight ratio of co-solvent, but the particle size distribution was broader. The standard deviation of particle diameter is large when the co-solvent weight ratio is more than 0.35 and less than 0.15. However, the specific surface area was similar for all weight ratios ranging from 1000 to 1300 m2/g. The synthesized silica was spherical and has high specific surface area. The cobalt was impregnated onto the obtained silica to produce the cobalt catalyst used for CO2 hydrogenation.</